2015
DOI: 10.1002/hed.24198
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal treatment of xerostomia, odor, and taste abnormalities in patients with head and neck cancer

Abstract: Our results demonstrate that using nonpharmaceutical liposomal sprays improve smell, taste, and symptoms of xerostomia in patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1232-E1237, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Different application forms (mouth spray, nose spray, eye spray) have been used to treat xerostomia, rhinitis sicca and keratoconjunctivitis sicca in 73 patients an significant improvement could be achieved [11]. Results from another trial in patients after treatment of head and neck cancer demonstrated that a liposomal spray could improve smell and taste disorders in addition to xerostomia [23].…”
Section: Discussionmentioning
confidence: 99%
“…Different application forms (mouth spray, nose spray, eye spray) have been used to treat xerostomia, rhinitis sicca and keratoconjunctivitis sicca in 73 patients an significant improvement could be achieved [11]. Results from another trial in patients after treatment of head and neck cancer demonstrated that a liposomal spray could improve smell and taste disorders in addition to xerostomia [23].…”
Section: Discussionmentioning
confidence: 99%
“…They easily fuse with the cell membrane of the nasal mucosa to form a natural defense [12]. Phospholipid surfactants are bene cial for reducing the surface tension at the nasal air-mucus interface and lubricating the nasal cavity, increasing the ciliary beat frequency, reducing the adhesion of pathogenic microorganisms or allergens, stabilizing the barrier of the respiratory tract and enhancing the anti-in ammatory and wound-healing capacities of the upper airway mucosa, including the nasal mucosa [12][13][14][15][16][17].…”
Section: Potential Mechanisms Of Surfrin®mentioning
confidence: 99%
“…They make up most of the protective nasal surfactant layer [12,13]. Liposomes, which consist of phospholipids, can protect the nasal mucous membrane by complementing the lipid layer [14], removing antigens and improving mucociliary clearance by mechanical cleansing [13,15], and aid in healing the damaged nasal mucosa by covering the surface of the mucosa [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutics based on lecithin as principal component (e.g. nasal spray and inhalation solution) have been shown to be effective in the treatment of various health disorders, such as allergic rhinitis [ 43 ], rhinitis sicca [ 45 , 47 ], sinunasal symptoms [ 48 ], and care after tracheostomy [ 49 ]. Chronic respiratory disease e.g.…”
Section: Introductionmentioning
confidence: 99%